CRITICAL REGION - SEMAPHORE MUTEX DALAM CPU OS SIMULATOR V.7.2.27. - Hariningsih, S P (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2013)
Operating system is a in computer program that regulates the resourcein a computer . The operating systems should monitor the status of each resource, decide which process has to get those resources, allocate resources, and claim back when it has done. To implement the process model, the operating system use a table / array called table with one entry for each process. Each entry contains the status of the process, the program counter, stack pointer, memory allocation, file status, scheduling information, etc. Wich from employment to ready status. In multiprogramming system, the processor also switch from one program to another program, run the program in a few milliseconds. At any given time, the processor is actually just did a program, but in a second of accumulation time, the processor was working on several programs, so the program look run in parallel. Critical region is a port of a program being access memory accordingly. Critical region happere on a mutual exclussion process, which is only one process being execute. Neverthless, there is a certain that we call race condition. It is a situation where some processes are access and manipulate the data accordingly. Thos, we have to pind some methode to prevent leftover process in writing process and reading process for data shared accordingly, at is mutual exclussion. It will examined on OS CPU simulator. Althought it can prevent the race conditions, it isn’t enough to do cooperation between some proces in parallel efficiently in using data shared.